Bis{2′-[1-(2-hydroxyphenyl)ethylidene]-benzohydrazido} bis(pyridine-κN)zinc(II) - Basirun, Wan Jefrey; Yamin, B.M.; Ali, H.; Khamis, N.A. (International Union of Crystallography, 2004)
In the centrosymmetric title compound, [Zn(C15H 13N2O2)2-(C5H 5N)2], the Zn atom is chelated by the O and N atoms of two bidentate ligands. The coordination geometry of the central Zn atom is octahedral. The crystal packing is stabilized by intermolecular C - H⋯O interactions. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.